44.2k views
4 votes
Find the
Prove that sin theta tan theta= (1 + sec theta)(1 - cos theta)


User Lisle
by
5.8k points

2 Answers

4 votes
Sin tita tan tita = LHS
User Daniel Kaplan
by
5.4k points
7 votes

Answer:

Explanation:

RHS = (1 +Sec Ф)(1 - Cos Ф)

= 1*1 - 1*Cos Ф + Sec Ф *1 - Sec Ф *Cos Ф

= 1 - Cos Ф + Sec Ф - 1 {Sec Ф =
(1)/(Cos \ theta) )

=Sec Ф - Cos Ф

=
(1)/(Cos \ theta) - Cos Ф


= (1)/(Cos \ theta)-(Cos \ theta*Cos \ theta)/(Cos \ theta)\\\\= (1-Cos^(2) \ theta)/(Cos \ theta)\\\\= (Sin^(2) \ theta)/(Cos \ theta)\\\\=(Sin \ theta*Sin \ theta)/(Cos \ theta)\\\\= Sin \ theta*(Sin \ theta)/(Cos \ theta)

= Sin Ф* tan Ф = LHS

User Ken Mason
by
5.3k points